Upaya Penyelesaian Pembunuhan Akibat Sengketa Tanah Ulayat Melalui Mekanisme Hukum Adat Di Wilayah Adonara Kabupaten Flores Timur - Maria Penaten Peran; Karolus Kopong Medan; Adrianus Djara Dima (Law Faculty, Nusa Cendana University, 2026)
This empirical legal research analyzes the causes and solutions to murder cases that occurred due to customary land conflicts in Adonara, East Flores, focusing on the dispute between Lewobunga and Lewonara Villages (2012) that has its roots since the 1930s. The findings show that there are five main causes: (1) unclear land boundaries caused by natural markers (such as trees or stones) that are not permanent, (2) differences in historical stories regarding ownership between the two villages, (3) lack of recognition of property rights from other parties, (4) inherited grudges that ignore the customary principle of tubak Belo (a duel that determines truth according to the religious values ​​of Rera Wulan Tanah Ekan), and (5) low government involvement in mediation and boundary determination. Efforts to achieve resolution through customary law practices and the role of customary leaders as mediators are faced with various challenges: the community's belief that tubak Belo is a legitimate method, distrust of the formal legal system, and interference from outside parties. In conclusion, to achieve lasting peace, it is necessary to combine local wisdom (customs) with clear boundary enforcement by the government.